Pembuatan Situs Web Pusat Kebudayaan Betawi dengan Menggunakan PHP dan MySQL - Bay Haqi; Junita Yosephine Sinurat; Mima Nizma (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
The World Wide Web is rapidly developing in many aspects of human life. At first, the development of the World Wide Web is only a static information exchange in which the recipient and provider of informationonlyestablish one-way communication. The recipient only gets information from the information providerswithoutinteracting with them. This kind of system is usually calledthe static web. Further, the Betawi cultural center site is trying to develop itself by creating the more interactive and interesting web that can help many people who want to know Betawi culture easily get information. This site also tries to make digital documentation so that the Betawi culture can be known by the public and be saved from extinction due to rapid development of the era.